PROBLEMS OF DEVELOPMENT OF SYSTEM OF HOUSING CONTROL IN URBAN SETTLEMENTS - M. Stadolin (Вестник университета)
The article analyses the existing system of housing control, reveals modern problems and peculiarities of state supervision and municipal control in the housing sector of urban settlements, proposed measures for further development of the system of control over the provision of housing services.